Innexins: Expression, Regulation, and Functions - Güiza, Juan; Barría, Iván; Sáez, Juan C.; Vega, José L. (Frontiers in Physiology, 2018)
The innexin (Inx) proteins form gap junction channels and non-junctional channels (named hemichannels) in invertebrates. These channels participate in cellular communication play-ing a relevant role in several physiological processes. Pioneer studies conducted mainly in worms and flies have shown that innexins participate in embryo development and behavior. However, recent studies have elucidated new functions of innexins in Arthropoda, Nema-toda, Annelida, and Cnidaria, such as immune response, and apoptosis. This review de-scribes emerging data of possible new roles of innexins and summarizes the data available to date.